2016
DOI: 10.5114/fn.2016.62535
|View full text |Cite
|
Sign up to set email alerts
|

Administration of vitamin D 3 induces CNPase and myelin oligodendrocyte glycoprotein expression in the cerebral cortex of the murine model of cuprizone-induced demyelination

Abstract: A b s t r a c t In the central nervous system (CNS) the main proteins of myelin are proteolipid protein (PLP), myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG) and CNPase. Myelin oligodendrocyte glycoprotein is a minor component of the myelin sheath, but is an important autoantigen linked to the pathogenesis of multiple sclerosis (MS). CNPase is expressed exclusively by oligodendrocytes in the CNS, and the appearance of CNPase seems to be one of the earliest events of oligodendrocyte diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The present results showed that the expression levels of IL-1β and NLRP3 were decreased by clemastine (H1 receptor antagonist), but the expression of HH1R was unaffected and localized in the microglia. The OPCs include NG2 and PDGFR-α cells, which differentiate progressively in a multiprocess morphology and sequentially bind to anti-CNPase and anti-MBP antibodies [26][27][28]. Through differentiation and maturation, OPCs migrate to myelinated target axons to form myelin.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that the expression levels of IL-1β and NLRP3 were decreased by clemastine (H1 receptor antagonist), but the expression of HH1R was unaffected and localized in the microglia. The OPCs include NG2 and PDGFR-α cells, which differentiate progressively in a multiprocess morphology and sequentially bind to anti-CNPase and anti-MBP antibodies [26][27][28]. Through differentiation and maturation, OPCs migrate to myelinated target axons to form myelin.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 159–162 , 266 Indeed, animals suffering from neurodegeneration showed increased expression of MBP, MOG and PLP upon cholecalciferol or calcitriol treatment compared with vehicle control. 159 , 160 , 266 , 267 Similarly, calcitriol treatment reduced OPC proliferation and lead to higher oligodendrocyte differentiation with consequent increase in MBP production in vitro . 133 , 266 In addition, rats suffering from ethidium–bromide induced demyelination showed decreased caspase-3 activation in the CNS when treated with calcitriol, suggesting also a beneficial effect of VitD on oligodendrocyte apoptosis in multiple sclerosis.…”
Section: Vitd Actions In the Cnsmentioning
confidence: 99%
“…Similar nutrient mixtures or single nutrients may therefore be beneficial in supporting white matter in aging through provision of precursors and cofactors for myelin membrane synthesis. Many other nutrients have also shown beneficial effects on white matter protection in the context of damage or demyelination, including sphingomyelin (191), vitamins K and D (192)(193)(194), and taurine (195). While the benefit of such nutrient support in the non-pathological aging brain remains hypothetical, there is strong evidence that nutritional interventions can be beneficial in the context of white matter repair following injury and demyelination, and in protecting cognitive function in pathologies associated with white matter, therefore their utility in promoting healthy aging through oligodendrocyte support warrants further research.…”
Section: Beneficial Effects Of Dietary Interventions In Demyelinating Conditions Such As Ms Andmentioning
confidence: 99%